Is underwater endoscopic mucosal resection of colon polyps superior to conventional techniques? A network analysis of endoscopic mucosal resection and submucosal dissection - Tan, Darren Jun Hao; Ng, Cheng Han; Lim, Xiong Chang; Lim, Wen Hui; Yuen, Linus Zhen Han; Koh, Jin Hean; Nistala, Kameswara Rishi Yeshayahu; Ho, Khek-Yu; Chong, Choon Seng; Muthiah, Mark D. (Endoscopy International Open, 2022)
Background and study aims Evidence from recent trials comparing conventional endoscopic mucosal resection (EMR) to underwater EMR (UEMR) have matured. However, studies comparing UEMR to endoscopic submucosal dissection (ESD) are lacking. Hence, we sought to conduct a comprehensive network meta-analysis to compare the efficacy of UEMR, ESD, and EMR.Methods Embase and Medline databases were searched from inception to December 2020 for articles comparing UEMR with EMR and ESD. Outcomes of interest included rates of en bloc and complete polyp resection, risk of perforation and bleeding, and local recurrence. A network meta-analysis comparing all three approaches was conducted. In addition, a conventional comparative meta-analysis comparing UEMR to EMR was performed. Analysis was stratified according to polyp sizes (< 10 mm, ≥ 10 mm, and ≥ 20 mm).Results Twenty-two articles were included in this study. For polyps ≥ 10 mm, UEMR was inferior to ESD in achieving en bloc resection (P = 0.02). However, UEMR had shorter operating time for polyps ≥ 10 mm (P < 0.001), and ≥20 mm (P = 0.019) with reduced perforation risk for polyps ≥ 10 mm (P = 0.05) compared to ESD. In addition, en bloc resection rates were similar between UEMR and EMR, although UEMR had reduced recurrence for polyps ≥ 10 mm (P = 0.013) and ≥ 20 mm (P = 0.014). UEMR also had shorter mean operating than EMR for polyps ≥ 10 mm (P < 0.001) and ≥ 20 mm (P < 0.001). Risk of bleeding and perforation with UEMR and EMR were similar for polyp of all sizes.Conclusions UEMR has demonstrated technical and oncological outcomes comparable to ESD and EMR, along with a desirable safety profile. UEMR appears to be a safe and effective alternative to conventional methods for resection of polyps ≥ 10 mm.